The Determinants of Non-traditional Activities of Vietnamese Commercial Banks: The Role of Women, Private Sector and Foreign Investors - Do Doan Trang; Dao Le Kieu Oanh; Le Ngoc Thuy Trang; Wing-Keung Wong (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study investigates the determinants and their influence on non-traditional banking activities among commercial banks in Vietnam, measured by non-interest income. Using a panel dataset of 23 listed Vietnamese commercial banks from 2010 to 2021, the research applies various panel data estimation techniques, including OLS, FEM, REM and GLS, to address potential model specification issues. However, the two step Generalised Method of Moments (GMM) estimator is ultimately employed due to its robustness in handling endogeneity and dynamic relationships. The results reveal that operational efficiency, loan-to-deposit ratio and bank size positively impact non-traditional activities. In contrast, net profit margin, non-performing loan ratio and selected macroeconomic variables exert negative effects. Notably, the presence of women on the board of directors significantly moderates these relationships, reversing the impact of operational efficiency and macroeconomic factors. In addition, the study finds that banks in the private sector and those with foreign capital contributions demonstrate similar moderating patterns. However, the effects of equity dependence and capital adequacy differ from the baseline case. These findings highlight the importance of governance characteristics and ownership structure in shaping non-interest income strategies. The study offers new empirical evidence on the role of gender diversity on boards, private ownership, and foreign investor participation in influencing income diversification in the banking sector, particularly in an emerging market context.